Digging up concrescences: a hermeneutics for process archaeology. Issue 1 (1st January 2021) - Gallagher, Shaun
ABSTRACT: In this paper I build on the process philosophy of Whitehead and on enactive approachs to hermeneutics, to suggest that if we want to conceive of archaeological practice in terms of a process archaeology, then rather than characterizing it as 'digging up the past', it is better to think of it as digging up concrescences. From the perspective of enactive hermeneutics, no artifact (from past or present) is a completely determinate matter of fact; its meaning is enacted in an ecology of practices, and should be understood as part of a dynamical network (of uses and beliefs) that changes when viewed from different perspectives. To the extent that an artifact retains an affordance-related meaning, whether original or new, it remains a concrescence and is never reducible to a determinate matter of fact.